Analysis of the fishing effort of the Mexican longline tuna fleet operating in the Gulf of Mexico in 2004 - K Xolaltenco-Coyotl; MJ Dreyfus-Léon; E Almanza-Heredia; JAE Almanza-Heredia (Ciencias Marinas, 2010)
The Gulf of Mexico yellowfin tuna (YFT) longline fishing effort for 2004 was analyzed. The data used to describe the longline characteristics and estimate the catch efficiency of the vessels (catch in number of organisms per trip) were obtained from fishing reports made by onboard scientific observers from the Mexican Tuna Exploitation and Dolphin Protection Program, covering 100% of the trips. To compare the catch per trip and determine the main aspects influencing it, generalized linear models were applied. To explain differences in efficiency, the following explanatory variables were considered: boat, bait, equipment, area, trimester, type of hook, number of hooks, temperature, longline total length, gangion length, trip duration (number of days), number of sets per trip, gear deployment time, longline soaking time, and hauling time. The model explained 57.5% of the variability of the catch. The variables that had the greatest influence on efficiency were boat, bait, trimester, equipment, number of sets per trip, and trip duration. The variable boat was the most important, suggesting that the Mexican YFT fleet operating in the Gulf of Mexico could be heterogeneous. This variable may include the experience of the captain and/or crew, boat age, motor characteristics and maintenance, or even crew comfort. The results should be considered preliminary since only one year was analyzed.